Theoretical Model of Management Professional Self-Perfection of the Head of a Sport School - Kholostenko, Tetiana (Pedagogical Discourse, 2018)
In the article the theoretical model of the management of professional self-improvement leader-school education (children’s sports school), which consists of content-, scientific and administrative aspects of design practice is given. Content aspect – is the essence of meaningful management of professional self-improvement leader-school education (children’s sports school), formed at the state, municipal, intra-school and personal levels. Scientific and administrative aspects – is the object and the subject of scientific and theoretical foundations acmeological concept and principles of professional self-head-school education (children’s sports school). Design and practical aspect – it is practical achievements that are embedded on the basis of methods and - acmeological center: program, strategy and sub-model of professional self-perfection.